Morphometric characterization of the freshwater crab Potamon elbursi Pretzmann, 1962 in the Caspian Sea and Namak Lake hydrographic systems. Issue 1 (14th November 2017) - Kalate, Atefe; Keikhosravi, Alireza; Naderloo, Reza; Hajjar, Toktam; Schubart, Christoph D
Abstract: The freshwater crab Potamon elbursi Pretzmann, 1962 is widely distributed in northwestern Iran, occurring in two separate hydrographic systems, one draining into the Caspian Sea and a second into Namak Lake. A total of 192 specimens from the two drainage systems were analyzed: 122 specimens from the Caspian drainage and 70 specimens from the Namak Lake drainage. Fourteen measurements of body dimensions were taken for traditional morphometric analyses, and eight landmarks and two semi-landmarks from the carapace were used for geometric-morphometric analyses. Morphometric analyses were performed with the aid of SPSS ver. 22 and geometric analyses using PAST ver. 2.14 and MorphoJ ver. 1.06d software. Adults and juveniles were separated using the K-means method, and puberty-size calculations revealed females reach morphometric puberty at smaller sizes than males. Sexual size dimorphism (SSD) and allometric growth findings revealed that males have longer carapaces, higher body height, and larger chelae, probably due to optimizing mating with females, whereas females have broader pleonal somites and a wider posterior carapace, likely because of more energy investment in egg care and reproduction. Although separate comparison of sexes between the two drainages showed no significant differences between females (in traditional morphometry), population comparisons (excluding pleonal characters) provide evidence for a significant distinction with partial overlapping. Poor dispersal ability and philopatric behaviour, as often known to occur in freshwater crabs, is probably responsible for such intraspecific differentiation in P. elbursi .